G356 Decision making management guideline for patients (<19 y) with idiopathic thickened pituitary stalk and/or idiopathic central diabetes insipidus. (12th March 2018) - Cerbone, M; Visser, J; Bulwer, C; Ederies, A; Kamali, I; Grossman, A; Korbonits, M; Spoudeas, HA
Abstract : Aim: To develop a guideline for the investigation and management of children and young people up to the age of 19 years with idiopathic thickened pituitary stalk (iTPS) and/or central diabetes insipidus (iCDI) where the aetiology is not apparent at presentation. Methods: The guideline development group (GDG) identified the objectives and the clinical questions which needed to be addressed. These were reviewed by guideline stakeholders and used to direct a systematic literature search. Published evidence was appraised using the GRADE system. Where the literature search identified sufficient evidence, the GDG made a guideline recommendation. Where there was insufficient evidence, the GDG drafted recommendations based on their expert opinion and reviewed these using a formal Delphi consensus process. This was a joint society (BSPED/CCLG) multidisciplinary national endeavour done to NICE methodology and overseen by RCPCH. Results: The literature search identified 568 articles covering the period Jan 1990 –March 2017. The most commonly reported causes of iTPS and iCDI in children are Langerhans Cell Hystiocytosis (LCH), Germ Cell Tumours (GCT) and craniopharingioma (CP). The average prevalence of LCH, GCT and CP in 11 case series (including 741 patients) is 16%, 13% and 12%, respectively. Overall, congenital defects are responsible for 19% of the iTPS/iCDI cases, whilst infectious diseases (2%), trauma (1%) and inflammatory/autoimmune conditions (1%) rarely occur in children. In 29% of the cases no aetiology is identified. Causes of pituitary stalk lesions in adults, metastatic tumours and neurosarcoidosis, do not form part of the differential diagnosis in children. What constitutes a TPS is not consistently defined across studies. High quality evidence was lacking for the majority of the clinical questions and two rounds of Delphi consensus were undertaken. A decision-making flowchart has been developed and will accompany the guideline. Conclusion: The likely aetiology of iTPS and iCDI in children differs from that in adults and justifies the development of age appropriate decision making management guidelines to inform best practice nationally. This will form the basis for future audits of practice and outcomes and is intended to improve the quality of care of children and young people with iTPS and iCDI.